Leibniz’s and Herder’s philosophy of optimism - Gluchman Vasil (Ethics & Bioethics (in Central Europe), 2021)
The author studies Leibniz’s views of vindicating God for the existence of evil in the world, as well as the idea of the best of all possible worlds, including the past and present criticism. Following Leibniz, he opted for the presentation of Herder’s philosophy of history as one of the most significant forms of philosophical optimism that influenced the first half of the 19th century, including contemporary debates on and critiques of the topic. He defines Herder’s concept as the philosophy of historical progress, which also significantly influenced Slovak philosophy of the given period. The main goal of the article is to present Leibniz’s and Herder’s views as a starting point for the Slovak philosophy of optimism and historical progress of the 18th century and the first half of the 19th century.